Pengaruh Kearifan Lokal dalam Penilaian Risiko Konstruksi - Iriyanto, Santje Magdalena; Sitorus, Yannice Luma Marnala (Department of Civil Engineering, Diponegoro University, 2023)
One of the obstacles to construction work in Papua is delays in implementation due to obstruction byindigenous communities at the project site. Understanding the implementation of construction work in atraditional area, especially those related to local wisdom, is one of the risk knowledge which is the first step inrisk conceptualization and is the aim of this research. A qualitative approach, which will elaborate on socialand cultural meanings to explain one of the phenomena that occurs in the world of construction in Papua, anddescriptive methods, are used in analyzing research data. The characteristics of the traditional territory wherethe project location is located also influence the construction risk value of a project. Based on the topographiccharacteristics of the region, there are four large groups of Papuan indigenous people, so there are differencesin the construction risk values faced according to the socio-cultural characteristics of each traditionalcommunity. Urban areas have a high construction risk and rural areas have a lower risk. The risk value ofconstruction projects in Papua is also influenced by the type of construction project which will be related tothe required land pattern.